Implementation of Fuzzy Functions Aimed at Fairer Grading of Students' Tests - Vanya Ivanova; Boyan Zlatanov (MDPI AG, 2019)
The main goal of this research is to achieve fairer assessment of students’ knowledge and skills in tests in view of the fact that learners with similar abilities are often assigned different test grades if their achievements are borderline cases between two grades. As an example, a student who has scored 29 points out of 60 in a test will fail, while another one with 30 or 31 points will pass, which can be viewed as unjust. This problem is addressed by using fuzzy logic and different fuzzy functions to determine whether students with borderline test scores are assigned the higher or the lower grade of the two. Furthermore, although changing the grades of individual students, the authors endeavor to preserve the overall score of all test takers statistically unchanged.